Body size explains interspecific variation in size–latitude relationships in geographically widespread beetle species. (20th October 2018) - Tseng, Michelle; Soleimani Pari, Sina
Abstract : 1. In most birds and mammals, larger individuals of the same species tend to be found at higher latitudes, but in insects, body size–latitude relationships are highly variable. 2. Recent studies have shown that larger‐bodied insect species are more likely to decrease in size when reared at increased temperature, compared with smaller‐sized species. These findings have led to the prediction that a positive relationship between body size and latitude should be more prevalent in larger‐bodied insect species. 3. This study measured the body size of > 4000 beetle specimens (12 species) collected throughout North America. Some beetle species increased in size with latitude, while others decreased. Importantly, mean species body size explained c . 30% of the interspecific variation in the size–latitude response. 4. As predicted, larger‐bodied beetle species were more likely to show a positive relationship between body size and latitude (Bergmann's rule), and smaller‐bodied species were more likely to show a negative body size–latitude relationship (inverse Bergmann's rule). 5. These body size–latitude patterns suggest that size‐specific responses to temperature may underlie global latitudinal distributions of body size in Coleoptera, as well as other insects. Abstract : In many birds and mammals, larger individuals of the same species tend to be found at higher latitudes (Bergmann's rule), but in insects, the relationship between body size and latitude is highly variable. More than 4000 beetles were measured across 12 species and it was found that smaller‐bodied species decreased, but larger‐bodied species increased in size with increasing latitude. These data suggest that the relationship between body size and temperature may help to explain interspecific variation in Bergmann's rule.